Psychiatric Advance Directives and their relevance to improving psychiatric care in Asian countries. (23rd December 2019) - Poremski, Daniel; Alexander, Mark; Fang, Tina; Tan, Giles Ming‐Yee; Ong, Samantha; Su, Alex; Fung, Daniel; Chua, Hong Choon
Abstract: People with mental illness may be unable to provide critical input about the care they wish to receive during a psychiatric crisis because of altered mental states. It is therefore imperative that clinicians seek to understand service users' wishes for care while they are well and able to provide meaningful input into the discussion. Achieving such an end may be done by discussing and completing a psychiatric advance directive. However, very few Asian countries have legislation that supports such advance directives. The present article seeks to give physicians more information about advance psychiatric directives and the potential role they could play to improve the healthcare provided in Asia to people at risk of losing capacity due to a mental illness. The degree to which mental health legislation supports psychiatric advance directives is documented for each country of South East Asia and Eastern Asia.